Is social auditing a key tool for achieving sustainable development goals? A study of Malaysian-listed companies - Nurulasyikin Binti Hassan (Tanjung Malim, 2024)
Is social auditing a key tool for achieving sustainable development goals? A study of Malaysian-listed companies by Nurulasyikin Binti Hassan